DO PRODUCT RECALLS HURT BRAND IMAGE? EVIDENCE FROM EVA PREMIUM BOTTLED WATER IN ILORIN METROPOLIS, NIGERIA: DO PRODUCT RECALLS HURT BRAND IMAGE? EVIDENCE FROM EVA PREMIUM BOTTLED WATER IN ILORIN METROPOLIS, NIGERIA - Bello, Kamal Asola (Economic Outlook, 2026)
Product recalls represent a double-edged sword that can hurt the recalling firm’s market value and create a dent in its brand image, while serving as a strategic signal of corporate responsibility when firms prioritize consumer safety over profit considerations. This study examines the effect of product recall practices on brand image, focusing on Eva Premium Bottled Water in the Ilorin metropolis. Adopting a positivist philosophy supported by a quantitative methodology, the study collected primary data through a structured and close-ended questionnaire administered to consumers and analysed using regression-based inferential statistics. The findings indicate that product recall frequency has a significant effect on brand perception, recall volume significantly influences brand positioning, and recall timing significantly impacts brand reliability. Accordingly, product recall practices significantly shape consumers’ evaluation of brand image. The study concludes that, when effectively managed, product recalls can enhance brand image by reinforcing consumer trust and signalling a firm’s commitment to public health and safety despite short-term reputational risks. The study recommends that brand managers adopt transparent communication strategies of timely announcements, clear explanations of recall causes, and detailed information on corrective measures during recall episodes. Aside from strengthening consumer confidence, such practices can reinforce the perception that consumer well-being takes precedence over profit maximization. While the study contributes to branding and crisis management literature, it acknowledges limitations related to geographic scope and reliance on self-reported consumer perceptions, suggesting future research incorporate multiple regions, industries, and complementary data sources.
Keywords: Product Recall, Brand Image, Recall Frequency, Brand Positioning, Recall Volume, Brand Reliability, Recall Timing